Epistemic Governance Social Change in the Modern World - Alasuutari, Pertti; Qadir, Ali (Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This book argues that modern governance is performed by actors who seek social change epistemically, by drawing on widespread, public views of reality. Agents of change such as parliamentarians or social movement activists will assess and affect what they believe to be people's conceptions of what is possible, rational, and desirable. This often means that these key authority figures will invest in credible knowledge production, as well as appeal to individual and group identifications, emotions, and values. Alasuutari and Qadir show how this epistemic governance works in three important arenas of social change: parliaments, which debate laws that constitute the bulk of reforms; international organizations that circulate global norms; and social movements and NGOs. Through their analysis, the authors' detailed, innovative methodology for discourse analysis indicates the utility of epistemic governance as a new paradigm for research into global social change. This book will be of use to students in upper level degree programs who want to design empirical research into social change as well as researchers in sociology, political science and public policy.